Soil pile structure interaction under SH wave excitation. - Koo, K.K (Earthquake engineering & structural dynamics.)
A continuum model for the interaction analysis of a fully coupled soil pile structure system under seismic excitation is presented in this paper. Only horizontal shaking induced by harmonic SH waves is considered so that the soil pile structure system is under anti plane deformation. The soil mass, pile and superstructure were all considered as elastic with hysteretic damping, while geometrically both pile and structures were simplified as a beam model. Buildings of various heights in Hong Kong designed to resist wind load were analysed using the present model. It was discovered that the acceleration of the piled structures at ground level can, in general, be larger than that of a free filled shaking of the soil site, depending on the excitation frequency. For typical piled structuresin Hong Kong, the amplification factor of shaking at the ground level does not show simple trends with the number of storeys of the superstructure, the thickness and the stiffness of soil, and the stiffness of the superstructure if number of storeys is fixed. The effect of pile stiffness on the amplification factor of shaking is, however, insignificant. Thus, simply increasing the pile size or the superstructure stiffness does not necessarily improve the seismic resistance of the soil pile structures system; on the contrary, it may lead to excessive amplification of shaking for the whole system.